PENGUKURAN KINERJA PERSONEL MFP LAW FIRM DENGAN METODE BALANCED SCORECARD (BSC): STUDI KASUS LAW FIRM DI JAKARTA - Firdaus, Mohamad; Indra Bakti (CV. Denasya Smart Publisher, 2025)
Accurate and structured performance assessment is an essential requirement for service-oriented organizations such as law firms. This study aims to develop a personnel performance measurement system at MFP Law Firm Jakarta using the Balanced Scorecard (BSC) approach. The BSC method was selected because it enables comprehensive performance evaluation from four perspectives: financial, customer, internal business processes, and learning and growth. The research was conducted by determining relevant performance indicators for each position within the law firm, namely Partner, Senior Lawyer, Junior Lawyer, Legal Staff, and Finance Staff. The assessment weights were set at 35% for the financial perspective, 25% for customer, 25% for internal business processes, and 15% for learning and growth. The results showed that the highest performance score was achieved by Personnel B (90.55), while the lowest was recorded by Pesonnel N (74.05). This system provides an objective overview of personnel performance achievements and can serve as a foundation for improving human resource management strategies within the law firm